Nasal delivery of H5N1 avian influenza vaccine formulated with GenJet™ or in vivo-jetPEI® induces enhanced serological, cellular and protective immune responses. (1st January 2018) - Cao, Weiping; Mishina, Margarita; Amoah, Samuel; Mboko, Wadzanai P.; Bohannon, Caitlin; McCoy, James; Mittal, Suresh K.; Gangappa, Shivaprakash; Sambhara, Suryaprakash
Abstract: Avian influenza virus infection is a serious public health threat and preventive vaccination is the most cost-effective public health intervention strategy. Unfortunately, currently available unadjuvanted avian influenza vaccines are poorly immunogenic and alternative vaccine formulations and delivery strategies are in urgent need to reduce the high risk of avian influenza pandemics. Cationic polymers have been widely used as vectors for gene delivery in vitro and in vivo . In this study, we formulated H5N1 influenza vaccines with GenJet™ or in vivo -jetPEI ®, and showed that these formulations significantly enhanced the immunogenicity of H5N1 vaccines and conferred protective immunity in a mouse model. Detailed analyses of adaptive immune responses revealed that both formulations induced mixed TH 1/TH 2 antigen-specific CD4 T-cell responses, antigen-specific cytotoxic CD8 T-cell and memory B-cell responses. Our findings suggest that cationic polymers merit future development as potential adjuvants for mucosal delivery of poorly immunogenic vaccines.